Determinants of individual income in EU countries: implications for social policy targeting - Baláková, Irena; Stávková, Jana; Hudec, Petr (Frontiers in Sociology, 2023)
Introduction The introduction of the Income Index constructed by authors as well as the identification of demographic, socio-economic and occupation-related factors influencing the income of individuals in EU countries is the main contribution of the paper. The Income Index makes it possible to analyze data of individuals from all EU countries. Methods The multiple hierarchical regression of EU-SILC microdata provides the factors that influence individuals’ income. Results Outcomes show through which factors can be intervened in social policy settings to reduce income inequality. Factors significantly affecting the Income Index are the household composition, occupation sector (typically agriculture and accommodation and services are related to low incomes) and the degree of urbanization (rural areas with the lowest incomes of individuals). Discussion Findings confirm ongoing discussions about the specific position of single parent households in the labour market and their need for social support.